Saliency and eye movements in the perception of natural scenes - Foulsham, Thomas (2008)
Humans inspect the environment around them by selecting a sequence of locations to fixate which will provide information about the scene. How are these locations chosen? The saliency map model suggests that points in the scene are represented topographically and that the likelihood of them being fixated depends on low-level feature contrast. This model makes specific predictions about the way people will move their eyes when looking at natural scenes, although there are few experimental tests of these predictions.